Hubungan Work Life Balance dan Motivasi terhadap Kinerja Karyawan Generasi Z di Kabupaten Klaten - Tegar Kurniawan; R. Taufiq Nur Muftiyanto; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The current transformation of the workplace demands that organizations be more adaptive in understanding the factors that influence employee productivity, especially among the younger generation. Generation Z, as an age group that is starting to dominate the workforce, brings different characteristics and needs, including in terms of work-life balance and motivation. They tend to value time more, opportunities for self-development, and an inclusive work environment that supports a balance between professional and personal life. This study aims to determine the relationship between work-life balance and motivation on the performance of Generation Z employees in Klaten Regency. This study used a quantitative approach with a survey method. A total of 100 respondents were selected using a purposive sampling technique based on age and employment status criteria. The research instrument was a questionnaire using a five-point Likert scale, which included statements related to the dimensions of work-life balance, levels of work motivation (both intrinsic and extrinsic), and employee performance indicators. Data were analyzed using IBM SPSS version 25 software with correlation tests and multiple regression. The results showed that both work-life balance and motivation have a positive and significant relationship on employee performance. Among these two variables, motivation is the dominant factor influencing performance improvement. This suggests that while work-life balance is important, internal employee motivations such as passion, purpose, and a sense of belonging have a greater impact on job performance. The implications of these findings suggest that companies need to design human resource management strategies that are not only flexible but also responsive to the needs of the younger generation. Creating a work environment that supports work-life balance, provides recognition, and provides career opportunities.